Korean language learning demotivation among EFL instructors in South Korea - Gearing, Nigel (Studies in Second Language Learning and Teaching, 2019)
Studies investigating the motivation of L1 speakers of English to learn the national language of the host society they currently reside in remain rare, despite the exponential growth of such individuals residing in these nations this century. Previous such studies in South Korea have concluded that learning Korean as a second language (L2) is largely perceived as difficult, unnecessary and is therefore accompanied by experiences of demotivation and amotivation (see Gearing & Roger, 2018). However, these studies did not explicitly address demotivation and amotivation when examining experiences that affect the motivation to learn Korean of 14 English as a Foreign Language (EFL) instructors working in South Korean university language education centers (LECs). Therefore, this study investigates which learning experiences resulted in the amotivation of participants and how two participants who experienced demotivation employed strategies to remotivate themselves. Coding of semi-structured interviews and optional diaries found that despite intent, most participants displayed symptoms of both amotivation and demotivation. The main implication of this study is that in the absence of perceived necessity, affected individuals with insufficient internal motivation or vision to acquire Korean consequently attribute externally related demotivating experiences to pre-existing or resulting amotivation.